2016
DOI: 10.1186/s40064-015-1597-z
|View full text |Cite
|
Sign up to set email alerts
|

MAP3K1-targeting therapeutic artificial miRNA suppresses the growth and invasion of breast cancer in vivo and in vitro

Abstract: Recent investigations have highlighted that therapeutic artificial microRNAs could be promising candidates for cancer therapy through the modulation of tumor promoter or suppressor. MEK kinase 1 (MEKK1) is expressed by mitogen-activated kinase kinase kinase 1 (MAP3K1), an important kinase that links Ras activation to MAPK signaling. In the present study, we showed that synthetic MAP3K1-targeting artificial miRNA may provide considerable beneficial effects in the prevention of breast cancer growth and metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…In addition to the expression of MAP3K1 in MCF7 cells, Liu et al reported the mRNA and protein expression of MEKK1 (MAP3K1) in two triple-negative breast cancer cell lines, in human MDA-MB-231 breast cancer cells, and another murine 4T1 breast cancer cells [64]. Furthermore, Liu et al showed that downregulation of MAP3K1 by MAP3K1targeting therapeutic arti cial microRNA (amiRNA), attenuated the proliferation and inhibited the migration and invasion of murine 4T1 breast cancer cells [64]. In the xenograft model of BALB/c-nude mice, MAP3K1 amiRNA suppresses tumor growth and decreases lung metastasis of murine 4T1 breast cancer cells [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the expression of MAP3K1 in MCF7 cells, Liu et al reported the mRNA and protein expression of MEKK1 (MAP3K1) in two triple-negative breast cancer cell lines, in human MDA-MB-231 breast cancer cells, and another murine 4T1 breast cancer cells [64]. Furthermore, Liu et al showed that downregulation of MAP3K1 by MAP3K1targeting therapeutic arti cial microRNA (amiRNA), attenuated the proliferation and inhibited the migration and invasion of murine 4T1 breast cancer cells [64]. In the xenograft model of BALB/c-nude mice, MAP3K1 amiRNA suppresses tumor growth and decreases lung metastasis of murine 4T1 breast cancer cells [64].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Liu et al showed that downregulation of MAP3K1 by MAP3K1targeting therapeutic arti cial microRNA (amiRNA), attenuated the proliferation and inhibited the migration and invasion of murine 4T1 breast cancer cells [64]. In the xenograft model of BALB/c-nude mice, MAP3K1 amiRNA suppresses tumor growth and decreases lung metastasis of murine 4T1 breast cancer cells [64]. These ndings indicate that MAP3K1 may play a role in the development and progression of triple-negative breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, recent studies have shown that MAP3K1 is functionally required for multiple physiological processes, including cell growth, cell migration, and apoptosis, and is strongly correlated with poor outcomes in a wide range of malignant cancers. [13][14][15] Furthermore,…”
Section: Discussionmentioning
confidence: 99%
“…The activation of MAPK networks includes 3 sequential phosphorylation strategies, from MAPK kinase kinases (MAP3Ks) to MAPK kinase (MAP2Ks) and MAPKs . Mitogen‐activated protein kinase kinase kinase 1 (MAP3K1), which is an important isoform for the first stimulation step of MAPKs, participates in regulating physiological and pathological processes, such as cell growth, cell migration, and apoptosis in gastric cancer, breast cancer, and nonsmall cell lung cancer cells . Additionally, a mechanistic study has indicated that MAP3K1 promotes tumor progression via the specific phosphorylation of MAP2K4 and thus selectively phosphorylates and activates c‐Jun N‐terminal kinase (JNK) .…”
Section: Introductionmentioning
confidence: 99%
“…We also found that TIPE2 decreased the expression of phosphorylated p38. It has been reported that p38 contributes to the proliferation and metastasis of breast cancer, and inhibition of p38 activation can suppress the growth and metastasis of breast cancer cells (25)(26)(27). Therefore, TIPE2 may suppress the tumorigenesis, growth and metastasis of breast cancer by inhibiting AKT and p38 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%